Cardiometabolic properties of telmisartan: new perspectives for use - O. M. Drapkina; E. I. Fomicheva (Рациональная фармакотерапия в кардиологии, 2015)
Modern clinical studies periodically open new prospects for the use of well-known products, lighting other facets of the point of application of these drugs. Application of the last representatives of sartans, not only as a drug with proven antihypertensive effect, but also in terms of their effects on metabolic processes, can be considered as such an example.